SERVICE QUALITY AND ITS IMPACT ON CUSTOMER SATISFACTION AND LOYALTY IN TRADITIONAL RETAIL - Arul Miftahul Firdaus (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study investigates the influence of service quality on customer satisfaction and loyalty within traditional retail settings, a sector increasingly challenged by digital disruption. Building on the SERVQUAL framework, this research employed a mixed-methods design that combined a large-scale quantitative survey (n = 400) with semi-structured interviews to capture both measurable relationships and contextual insights. Regression and factor analyses confirmed that service quality significantly predicts customer satisfaction, which in turn mediates the relationship between service quality and loyalty. Results indicate that intangible dimensions—empathy, responsiveness, and assurance—are equally, if not more, influential than tangible elements such as store layout and product availability. Approximately 75% of respondents expressed repeat purchase intentions when service quality exceeded expectations, highlighting the strategic importance of relational and experiential dimensions of retailing. The findings suggest that traditional retailers can strengthen competitiveness by integrating customer-centric training, relational service practices, and data-driven personalization. This study contributes to the literature by emphasizing the shifting weight of intangible service factors in fostering loyalty, while offering actionable insights for practitioners seeking to sustain customer relationships in an era dominated by e-commerce. Limitations include the focus on urban consumers and the cross-sectional design, pointing to the need for future research across diverse demographics and longitudinal contexts. Overall, the study underscores that superior service quality remains a cornerstone of customer retention and profitability in traditional retail.